Negotiating Nashville’s Norms: Women’s Place in Post-9/11 Country Music - Stafford, T. A. (2023)
Whilst much literature exists on significant episodes of country music history such as the Chicks controversy and the emergence of the ‘bro-country’ subgenre, limited attention has been spent exploring how these events may be connected, and what they reveal about Nashville’s understanding of the significance and place of its female stars. By examining the breadth of the country scene since 9/11, from lyrical analyses to understanding prevailing musical trends, this dissertation explores the position and power of Nashville’s female artists. The dissertation is split into three case studies. The first chapter addresses the Chicks controversy, the second bro-country, and the final investigates why some of Nashville’s biggest female stars have recently moved away from country and have instead engaged more with other genres. These case studies reveal a pattern in post-9/11 country music wherein male voices have not just become dominant, but also, oftentimes, speak on behalf of women. Ultimately, the dissertation establishes that the power of Nashville’s female artists has significantly reduced when compared to the late-1990s, a scenario made possible only by a country music culture that values women’s voices less, and thus prioritises male country singers on issues from radio playtime to awards nominations.